The Stringent Response Contributes to Persistent Methicillin-Resistant Staphylococcus aureus Endovascular Infection Through the Purine Biosynthetic Pathway - Li, Liang (J Infect Dis, 2020)
Persistent methicillin-resistant Staphylococcus aureus (MRSA) endovascular infections represent a significant clinical-therapeutic challenge. Of particular concern is antibiotic treatment failure in infections caused by MRSA that are “susceptible” to antibiotic in vitro. In the current study, we investigate specific purine biosynthetic pathways and stringent response mechanism(s) related to this life-threatening syndrome using genetic matched persistent and resolving MRSA clinical bacteremia isolates (PB and RB, respectively), and isogenic MRSA strain sets. We demonstrate that PB isolates (vs RB isolates) have significantly higher (p)ppGpp production, phenol-soluble-modulin expression, polymorphonuclear leukocyte lysis and survival, fibronectin/endothelial cell (EC) adherence, and EC damage. Importantly, an isogenic strain set, including JE2 parental, relP-mutant and relP-complemented strains, translated the above findings into significant outcome differences in an experimental endocarditis model. These observations indicate a significant regulation of purine biosynthesis on stringent response, and suggest the existence of a previously unknown adaptive genetic mechanism in persistent MRSA infection.